Design and Analysis of a Portable Robot for Venous Blood Sampling - Haoran Xue; Hasiaoqier Han; Gang Man; Zeran Feng; Peng Yu; Zhenbang Xu (Machines)
Venous blood sampling is a common procedure in medical diagnosis and treatment. However, the stationary manual blood sampling method in current use not only requires human resources but also is inconvenient for elderly persons and patients with limited mobility. To address this issue, this paper proposes a portable robot for venous blood sampling that features a 6-P-RR-R-RR horizontal parallel mechanism in its main structure. This design is better adapted to the shape of the human arm than previous robots, with an offset RR-hinge structure to increase the mechanism’s workspace. The introduction of offset hinge variables makes the kinematic solution more complex than that for conventional parallel mechanisms. This paper uses the kinematic constraint characteristics of the offset hinge to establish a kinematic model of the parallel mechanism, and the Newton–Raphson numerical iterative method is used to perform the computation. The kinematic model and its solutions are verified using kinematics simulation. The robot’s workspace is validated through special pose calculations and simulations to ensure that it meets the required specifications. A test system was built, and the accuracy of the parallel mechanism’s motion was verified.